Overall migration of microplastics in mineral water and non-alcoholic beverages - Kour, Jagjit; Bhatt, Pratima; Basnet, Shobha (BIBECHANA, 2023)
In today's world, packaging plays a crucial role in enhancing, enclosing, and shielding the materials that are used from procurement to handling and storage, processing, manufacturing and finally to the consumer. Packaging shields a product's contents from contamination, spoiling and makes it simple to store and transfer anywhere. Man-made plastic breaks down into little particles as a result of numerous external pressures. The degradation of plastics produce nano or microplastic. Health issues arise when microplastics (MPs) leak from plastic food packaging and are consumed by people. Though plastic packaging is abundant, consumers from developing nation are not aware of the risk associated with plastic food packaging. The purpose of this study is to demonstrate occurrence of microplastics in plastic food packaging and highlight the risks involved in consumption of microplastics. In this research, the migration of microplastics from different plastic containers were noted in accordance to the Bureau of Indian Standards IS - 9845-1998. The IS 9845: 1998 method was utilized in this investigation to determine the overall migration of various plastics used to package mineral water and beverages. Distilled water and 3% acetic acid (w/v) were utilized as food simulators for the analysis. The migration of microplastics in mineral water were found to range from 0.38 ppm to 0.54 ppm while in case of non-alcoholic beverages overall migration ranged from 0.29 to 75.75 ppm. Among the 12 samples of non-alcoholic beverages, one sample exceeded the maximum limit of microplastics as specified by WHO standard.microplastics